1995
DOI: 10.1103/physreve.52.642
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Dufour effect on convection in binary gas mixtures

Abstract: Linear and nonlinear properties of convection in binary uid layers heated from below are investigated, in particular for gas parameters. A Galerkin approximation for realistic boundary conditions that describes stationary and oscillatory convection in the form of straight parallel rolls is used to determine the in uence of the Dufour e ect on the bifurcation behaviour of convective ow intensity, vertical heat current, and concentration mixing. The Dufour{induced changes in the bifurcation topology and the exis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The results presented above can be compared with the linear stability analysis for this system [13,14,16]. For L 10 22 and c 20.24, the critical Rayleigh number is predicted to be r c 20.017.…”
Section: (Received 28 October 1997)mentioning
confidence: 94%
See 1 more Smart Citation
“…The results presented above can be compared with the linear stability analysis for this system [13,14,16]. For L 10 22 and c 20.24, the critical Rayleigh number is predicted to be r c 20.017.…”
Section: (Received 28 October 1997)mentioning
confidence: 94%
“…The linear stability analysis predicts that the critical wave number is zero [16], although further investigation has revealed that a broad spectrum of wave numbers becomes unstable slightly above threshold [14]. The initial patterns, such as the one shown in Fig.…”
Section: (Received 28 October 1997)mentioning
confidence: 99%
“…The governing equations are solved in ANSYS Fluent. The assumptions are taken for CFD modeling: the steady‐state conditions; no flux of energy due to a mass concentration gradient (no Duflor effects); work by viscous forces and by pressure is not done.…”
Section: Cfd Modelingmentioning
confidence: 99%
“…In presented CFD model the conservation and momentum equations in combination with source term for a porous medium equation are solved in ANSYS Fluent. The assumptions are taken for CFD modeling: steady‐state conditions; the temperature of flow is constant; no the flux of energy due to a mass concentration gradient (no Duflor effects); work by viscous forces and by pressure is not done; surface oxidation reactions of the metal wall are absent.…”
Section: Cfd Modelingmentioning
confidence: 99%